Aluminum-zirconium co-doped cobalt carbonate as well as preparation method and application thereof

Through the cobalt carbonate preparation method of aluminum-zirconium co-doped cobalt oxide, the problem of poor stability of lithium cobalt oxide cathode material at high voltage is solved, the high voltage cycling performance and structural stability of the material are improved, and the preparation process is simplified.

CN119219078APending Publication Date: 2024-12-31JINGMEN GEM NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411350316.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing lithium cobalt oxide positive electrode materials have stability problems at high voltages, the doping method is complex and the performance improvement is not obvious, and the poor electronic conductivity of conventional coating materials affects the capacity.

Method used

The cobalt carbonate preparation method of aluminum-zirconium co-doped is adopted. The doping amount of aluminum is gradually increased through two co-precipitation reactions, so as to achieve uniform doping of zirconium and improve the cycling performance of the material under high voltage.

Benefits of technology

The cyclic stability and specific capacity of lithium cobalt oxide positive electrode material at high voltage are improved, and the stability of the material structure is ensured, and the operation is simple and no additional preparation process is required.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219078A_ABST
    Figure CN119219078A_ABST
Patent Text Reader

Abstract

The invention provides aluminum-zirconium co-doped cobalt carbonate as well as a preparation method and application thereof. The preparation method comprises the following steps: adding a first cobalt-aluminum-zirconium solution and a precipitant solution into a reaction container in a parallel flow manner, and carrying out a first co-precipitation reaction; continuously adding the second cobalt-aluminum-zirconium solution into the first cobalt-aluminum-zirconium solution to obtain a third cobalt-aluminum-zirconium solution, simultaneously adding the third cobalt-aluminum-zirconium solution and the precipitator solution into the reaction container in a parallel flow manner, and carrying out a second coprecipitation reaction to obtain zirconium-aluminum co-doped cobalt carbonate; the concentration of aluminum salt in the first cobalt-aluminum-zirconium solution is smaller than that of aluminum salt in the second cobalt-aluminum-zirconium solution, and the concentration of zirconium salt in the first cobalt-aluminum-zirconium solution is the same as that of zirconium salt in the second cobalt-aluminum-zirconium solution; the feeding flow of the third cobalt-aluminum-zirconium solution is the same as that of the first cobalt-aluminum-zirconium solution. According to the preparation method disclosed by the invention, co-doping of aluminum and zirconium is realized, and the doping amount of aluminum is gradually increased in the cobalt carbonate growth layer, so that the performance of the lithium cobalt oxide positive electrode material under high voltage is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to aluminum-zirconium co-doped cobalt carbonate and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in consumer electronics, power tools, power storage, aerospace and other fields due to their core advantages such as high energy density, high power density and high safety performance. They are currently the fastest-growing and most promising new energy storage technology, and are also an important part of balancing energy and environmental issues. With the advancement of science and technology and the expansion of energy demand, the development of the next generation of lithium-ion batteries with higher energy density has become a top priority. Among them, the positive electrode material is the technical bottleneck that determines the energy density of the battery and accounts for more than one-third of the total cost of lithium-ion batteries. Therefore, research and development of lower-cost and higher-capacity positive electrode materials is one of the important development goals of lithium-ion battery technology. Among the commercialized positive electrode materials, the layered cobalt oxide lithium material has the highest energy density and is also the most competitive and possible positive electrode material for the next generation of lithium-ion batteries with higher energy density.

[0003] For lithium cobalt oxide materials, as the earliest commercialized positive electrode materials, the current large-scale commercialization level is still within 4.6V. There is still a certain gap between the actual discharge capacity and the theoretical capacity. Further improving the working cut-off voltage can improve the utilization rate of lithium ions and thus increase the discharge capacity and energy density. Therefore, the development of high-voltage lithium cobalt oxide modification technology is a hot topic of common concern in academia and industry.

[0004] From the perspective of bulk phase, at high voltage, especially above 4.55V, the bulk phase will undergo an incompletely reversible H3-M2 phase transition, resulting in drastic changes in unit cell parameters and lattice distortion, which can easily cause problems such as cracks and particle breakage. On the other hand, the surface stability of lithium cobalt oxide will also be affected by multiple factors under high voltage, thus affecting the electrical properties of lithium cobalt oxide materials.

[0005] Surface coating can effectively improve the stability of lithium cobalt oxide materials under high voltage, but the conventional fluoride, phosphate, oxide and other types of materials used for coating have poor electronic conductivity, so the coating will have a certain impact on the capacity of the material; for example, CN103390748A discloses a method for preparing an alumina-coated lithium cobalt oxide positive electrode material, which can form an Al2O3 inert layer on the surface of the lithium cobalt oxide material, inhibit the corrosion of the electrolyte on the positive electrode material, and improve the cycle performance of the material. The raw material composition and product formula are easy to control and suitable for large-scale production. However, the Al2O3 inert layer has the disadvantages of low ionic conductivity and large interface impedance, which will affect the capacity of the lithium cobalt oxide material to a certain extent.

[0006] In addition to surface coating, the stability of lithium cobalt oxide under high voltage can also be improved by doping. For example, CN105591081A discloses a high-voltage and high-rate lithium cobalt oxide positive electrode material and its preparation method, which uses cobalt oxide and lithium carbonate as precursors, adds magnesium carbonate, and obtains lithium cobalt oxide after the first sintering and crushing; then adds a mixed alcohol solution of alcohol aluminum and titanate, mixes and performs a second sintering to obtain the lithium cobalt oxide. Although the solution provided by the above document can improve the stability of lithium cobalt oxide under high voltage to a certain extent, the added Al and Mg belong to solid phase doping, the amount of doping is small, the doping is uneven, and repeated calcination is required. The process is complicated, resulting in an insignificant performance improvement effect.

[0007] Therefore, how to improve the performance of lithium cobalt oxide positive electrode materials under high voltage is a technical problem that needs to be solved urgently. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an aluminum-zirconium co-doped cobalt carbonate and a preparation method and use thereof. The preparation method provided by the present invention realizes aluminum-zirconium co-doping, and while cooperating with each other, it also gradually increases the amount of aluminum doping in the cobalt carbonate growth layer. The preparation method does not require an additional preparation process and is simple to operate, thereby improving the performance of lithium cobalt oxide positive electrode materials under high voltage.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing aluminum-zirconium co-doped cobalt carbonate, the preparation method comprising the following steps:

[0011] Adding the first cobalt-aluminum-zirconium mixed salt solution and the precipitant solution into a reaction container in parallel to perform a first coprecipitation reaction to obtain a crystal nucleus structure;

[0012] After the first coprecipitation reaction is completed, the second cobalt-aluminum-zirconium mixed salt solution is continuously added to the first cobalt-aluminum-zirconium mixed salt solution to obtain a third cobalt-aluminum-zirconium mixed salt solution, and the third cobalt-aluminum-zirconium mixed salt solution and the precipitant solution are simultaneously added to the reaction container in parallel to perform a second coprecipitation reaction to obtain the zirconium-aluminum co-doped cobalt carbonate;

[0013] Among them, the concentration of aluminum salt in the first cobalt-aluminum-zirconium mixed salt solution is lower than the concentration of aluminum salt in the second cobalt-aluminum-zirconium mixed salt solution, and the concentration of zirconium salt in the first cobalt-aluminum-zirconium mixed salt solution is consistent with the concentration of zirconium salt in the second cobalt-aluminum-zirconium mixed salt solution; the feed flow rate of the third cobalt-aluminum-zirconium mixed salt solution is consistent with the feed flow rate of the first cobalt-aluminum-zirconium mixed salt solution in the first coprecipitation reaction process.

[0014] It should be noted that the standard for obtaining the crystal nucleus structure in the present invention is that the particles begin to grow from the crystal nucleus without generating a new crystal nucleus structure, and the specific particle size of the crystal nucleus structure can be adaptively selected and adjusted according to the target particle size of the product.

[0015] The preparation method provided by the present invention obtains a stable crystal nucleus structure, and then controls the cobalt-aluminum-zirconium mixed salt solution, which can better ensure that the aluminum in the cobalt carbonate particles gradually increases as the particles grow, and in the second coprecipitation preparation process, the second cobalt-aluminum-zirconium mixed salt solution with a higher aluminum salt concentration is directly added to the aluminum salt solution with a lower aluminum salt concentration at a fixed feed flow rate, which can continuously increase the concentration of aluminum salt in the third cobalt-aluminum-zirconium solution without affecting the normal progress of the reaction, and at the same time, the zirconium salt concentration is kept consistent in the two mixed salt solutions, thereby achieving uniform doping of zirconium; thereby, in the obtained aluminum-zirconium co-doped cobalt carbonate material, the aluminum doping amount gradually increases in the cobalt carbonate growth layer, and the zirconium presents a uniform doping pattern, which can not only ensure the structural stability of the cobalt carbonate material, but also effectively improve the cycle performance of the lithium cobalt oxide material under high voltage, and at the same time ensure the good performance of the first effect of the lithium cobalt oxide material; and the preparation method does not require an additional preparation process and is simple to operate.

[0016] In the present invention, if a stable crystal nucleus structure is not obtained first and then the aluminum salt concentration is regulated, the aluminum doping amount in the cobalt carbonate material cannot be increased regularly, resulting in irregular segregation of aluminum doping, which in turn affects the performance; and if the concentration of aluminum salt in the first cobalt aluminum zirconium mixed salt solution is greater than or equal to the concentration of aluminum salt in the second cobalt aluminum zirconium mixed solution, it is impossible to control the amount of aluminum added during the first coprecipitation reaction, thereby affecting the formation of the gradually increasing structure of aluminum.

[0017] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0018] Preferably, the concentration of the first cobalt-aluminum-zirconium mixed salt solution and the concentration of the second cobalt-aluminum-zirconium mixed salt solution are each independently 1.8 to 1.9 mol / L, for example, 1.8 mol / L, 1.83 mol / L, 1.85 mol / L, 1.88 mol / L or 1.9 mol / L, etc., but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] In the present invention, it is further preferred that the concentration of the first aluminum-zirconium mixed salt solution and the concentration of the second cobalt-aluminum-zirconium mixed salt solution are kept consistent, so as to better ensure the concentration control of aluminum and zirconium.

[0020] Preferably, the concentration of zirconium salt in the first cobalt-aluminum-zirconium mixed salt solution is 4.8-5.4 mmol / L, for example, 4.8 mmol / L, 4.9 mmol / L, 5 mmol / L, 5.1 mmol / L, 5.2 mmol / L, 5.3 mmol / L or 5.4 mmol / L, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] Preferably, the concentration of aluminum salt in the first cobalt-aluminum-zirconium mixed salt solution is 10.8-12 mmol / L, for example, 10.8 mmol / L, 10.9 mmol / L, 11 mmol / L, 11.1 mmol / L, 11.2 mmol / L, 11.3 mmol / L, 11.4 mmol / L, 11.5 mmol / L, 11.6 mmol / L, 11.7 mmol / L, 11.8 mmol / L, 11.9 mmol / L or 12 mmol / L, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the concentration of aluminum salt in the second cobalt-aluminum-zirconium mixed solution is 37.5-40mmol / L, for example, 37.5mmol / L, 37.8mmol / L, 38mmol / L, 38.3mmol / L, 38.5mmol / L, 38.8mmol / L, 39mmol / L, 39.3mmol / L, 39.5mmol / L, 39.8mmol / L or 40mmol / L, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] In the present invention, the concentration of aluminum salt in the first cobalt-aluminum-zirconium mixed salt solution is further regulated to be 10.8-12 mmol / L, and the concentration of aluminum salt in the second cobalt-aluminum-zirconium mixed solution is 37.5-40 mmol / L, which can better control the total doping amount of Al in the material and make it present a regular gradient distribution.

[0024] Preferably, the feed flow rate L2 of the second cobalt, aluminum, zirconium mixed salt solution satisfies: 20L / h≤L2<L1, for example, 20L / h, 22.5L / h, 25L / h, 27.5L / h, 30L / h, 32.5L / h, 35L / h, 37.5L / h or 40L / h, etc., wherein the feed flow rate of the first cobalt, aluminum, zirconium mixed salt solution is L1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] It should be noted that L2 in the present invention is the feed flow rate of the second cobalt-aluminum-zirconium mixed salt solution into the first cobalt-aluminum-zirconium mixed salt solution.

[0026] In the present invention, the feed flow rate L2 of the second cobalt-aluminum-zirconium mixed salt solution satisfies: 20L / h≤L2<L1, which is more conducive to the gradient distribution of Al in the structure. If the feed flow rate is lower than 20L / h, it cannot be guaranteed that the third cobalt-aluminum-zirconium mixed salt solution will enter the reactor sufficiently in the later stage, resulting in an imbalance in flow matching, thereby affecting the normal reaction. If the feed flow rate exceeds the first cobalt-aluminum-zirconium mixed salt solution, the first cobalt-aluminum-zirconium mixing tank will be overfilled and overflow, and when the second cobalt-aluminum-zirconium mixed solution is completely injected into the first cobalt-aluminum-zirconium mixed solution, the Al concentration is fixed, and the gradient doping effect cannot be achieved.

[0027] Preferably, the reaction temperatures of the first coprecipitation reaction and the second coprecipitation reaction are independently 35-50°C, such as 35°C, 40°C, 45°C or 50°C, etc., but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] Preferably, the pH values ​​of the first coprecipitation reaction and the second coprecipitation reaction are each independently 6.9 to 8, for example 6.9, 7, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9 or 8, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] Preferably, the stirring speeds of the first coprecipitation reaction and the second coprecipitation reaction are each independently 150 to 450 rpm, for example, 150 rpm, 180 rpm, 200 rpm, 230 rpm, 250 rpm, 280 rpm, 300 rpm, 330 rpm, 350 rpm, 380 rpm, 400 rpm, 430 rpm or 450 rpm, etc., but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] In the present invention, “each independently” means that they may be the same or different.

[0031] As a preferred technical solution, the preparation method comprises the following steps:

[0032] Adding the first cobalt-aluminum-zirconium mixed salt solution and the precipitant solution into the reaction container at a feed flow rate of L1 in parallel to perform a first coprecipitation reaction to obtain a crystal nucleus structure;

[0033] A second cobalt-aluminum-zirconium mixed salt solution is continuously added to the first cobalt-aluminum-zirconium mixed salt solution, and the feed flow rate L2 of the second cobalt-aluminum-zirconium mixed salt solution satisfies: 20L / h≤L2<L1, to obtain a third cobalt-aluminum-zirconium mixed salt solution, and the third cobalt-aluminum-zirconium mixed salt solution and the precipitant solution are simultaneously added to the reaction container in parallel to perform a second coprecipitation reaction to obtain the zirconium-aluminum co-doped cobalt carbonate;

[0034] Among them, the concentration of aluminum salt in the first cobalt-aluminum-zirconium mixed salt solution is 10.8-12 mmol / L, and the concentration of aluminum salt in the second cobalt-aluminum-zirconium mixed salt solution is 37.5-40 mmol / L; the concentration of zirconium salt in the first cobalt-aluminum-zirconium mixed salt solution is consistent with the concentration of zirconium salt in the second cobalt-aluminum-zirconium mixed salt solution, and the concentration of zirconium salt in the first cobalt-aluminum-zirconium mixed salt solution is 4.8-5.4 mmol / L; the feed flow rate of the third cobalt-aluminum-zirconium mixed salt solution is consistent with the feed flow rate of the first cobalt-aluminum-zirconium mixed salt solution in the first coprecipitation reaction process.

[0035] It should also be noted that the preparation method provided by the present invention, the specific material types of the remaining preparation raw materials, preparation parameters and specific preparation process are all selected by conventional technology;

[0036] Optionally, the type of salt in the mixed salt solution includes but is not limited to at least one of sulfate, acetate, chloride or nitrate;

[0037] Optionally, the feed flow rate of the precipitant solution can be adaptively adjusted according to the feed flow rate of the raw salt solution in the preparation process; and the types of precipitants include but are not limited to at least one of ammonium carbonate, ammonium bicarbonate, sodium bicarbonate or sodium carbonate;

[0038] Optionally, after the second coprecipitation reaction is completed, the feeding is stopped, and then washing is performed, the washing process includes alkali washing and water washing, and after the washing is completed, drying is performed to obtain the aluminum-zirconium co-doped cobalt carbonate;

[0039] In addition to the limitations of the above technical features, those skilled in the art can make adaptive selections and adjustments in the preparation process of the preparation method provided by the present invention according to actual needs.

[0040] In a second aspect, the present invention provides an aluminum-zirconium co-doped cobalt carbonate, wherein the aluminum-zirconium co-doped cobalt carbonate is prepared by the preparation method described in the first aspect;

[0041] The aluminum-zirconium co-doped cobalt carbonate comprises an aluminum-zirconium co-doped crystal core and an aluminum-zirconium co-doped cobalt carbonate growth layer located on the surface of the crystal core; the doping amount of the aluminum in the cobalt carbonate growth layer increases from the inside to the outside.

[0042] In the aluminum-zirconium co-doped cobalt carbonate provided by the present invention, zirconium is uniformly doped in the cobalt carbonate material, and the doping amount (i.e., doping quality) of aluminum in the cobalt carbonate growth layer excluding the crystal nucleus is increased from the inside to the outside. The synergistic combination of zirconium and aluminum not only improves the cycle stability of the lithium cobalt oxide positive electrode material under high voltage (≥4.55V), but also ensures the specific capacity and structural stability of the lithium cobalt oxide positive electrode material.

[0043] In a third aspect, the present invention provides cobalt trioxide, which is obtained by sintering the aluminum-zirconium co-doped cobalt carbonate as described in the second aspect.

[0044] In the present invention, the method for preparing cobalt tetroxide from aluminum-zirconium co-doped cobalt carbonate is also a conventional technical solution, and the present invention is applicable to any preparation process that can be known within a reasonable range by those skilled in the art;

[0045] Specifically, in the process of sintering cobalt trioxide, the sintering can be one-stage sintering or segmented sintering;

[0046] Optionally, the heating rate of the one-stage sintering is 8 to 12°C / min, such as 8°C / min, 9°C / min, 10°C / min, 11°C / min or 12°C / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0047] Optionally, the temperature of the one-stage sintering is 600-750° C., such as 600° C., 650° C., 700° C. or 750° C., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0048] Optionally, the holding time of the one-stage sintering is 90 to 200 min, for example 90 min, 100 min, 130 min, 150 min, 180 min or 200 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] In a fourth aspect, the present invention provides a lithium cobalt oxide, which is obtained by mixing and sintering the cobalt oxide as described in the third aspect and a lithium source.

[0050] In the present invention, the preparation process of lithium cobalt oxide is also a conventional technical solution, and those skilled in the art can adaptively select and adjust it according to actual needs.

[0051] In a fifth aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the lithium cobalt oxide as described in the fourth aspect.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] The preparation method provided by the present invention obtains a stable crystal nucleus structure, and then regulates the cobalt-aluminum-zirconium mixed salt solution, which can better ensure that the aluminum in the cobalt carbonate particles gradually increases as the particles grow, and in the second coprecipitation preparation process, the second cobalt-aluminum-zirconium mixed salt solution with a higher aluminum salt concentration is directly added to the aluminum salt solution with a lower aluminum salt concentration at a fixed feed flow rate, which can continuously increase the concentration of aluminum salt in the third cobalt-aluminum-zirconium mixed salt solution without affecting the normal progress of the reaction, and at the same time, the zirconium salt concentration is kept consistent in the two mixed salt solutions, thereby achieving uniform doping of zirconium; thereby, in the obtained aluminum-zirconium co-doped cobalt carbonate material, the aluminum doping amount gradually increases in the cobalt carbonate growth layer, and the zirconium presents a uniform doping pattern, which can not only ensure the structural stability of the cobalt carbonate material, but also effectively improve the cycle performance of the lithium cobalt oxide material under high voltage, and at the same time ensure the good performance of the first effect of the lithium cobalt oxide material; and the preparation method does not require an additional preparation process and is simple to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is a schematic diagram of the preparation process of the second coprecipitation reaction provided in Example 1.

[0055] Figure 2 This is the EDS graph of zirconium on the surface of aluminum-zirconium co-doped cobalt carbonate provided in Example 1.

[0056] Figure 3 This is the EDS graph of aluminum in the surface of aluminum-zirconium co-doped cobalt carbonate provided in Example 1. DETAILED DESCRIPTION

[0057] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0058] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.

[0059] In the description of this application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0060] Example 1

[0061] This embodiment provides an aluminum-zirconium co-doped cobalt carbonate, and the preparation method of the aluminum-zirconium co-doped cobalt carbonate is as follows:

[0062] Step 1:

[0063] A first cobalt-aluminum-zirconium mixed salt solution A is prepared, wherein the concentration of the Co salt (cobalt chloride) in the solution A is 1.866 mol / L, the concentration of the aluminum salt (aluminum sulfate) in the solution A is 11.36 mmol / L, the concentration of the Zr salt (zirconium sulfate) in the solution A is 5.03 mmol / L, and the volume of the solution A is 960 L;

[0064] A second cobalt-aluminum-zirconium mixed salt solution B (chloride salt) is prepared, wherein the concentration of the Co salt (cobalt chloride) in solution B is 1.866 mol / L, the concentration of the aluminum salt (aluminum sulfate) in solution B is 38.77 mmol / L, the concentration of the Zr salt (zirconium sulfate) in solution B is 5.03 mmol / L, and the volume of solution B is 800 L;

[0065] The concentration of the precipitant ammonium bicarbonate solution C is prepared to be 2.78 mol / L;

[0066] Step 2:

[0067] The first cobalt-aluminum-zirconium mixed salt solution A was added to the reactor at a feed rate of 40 L / h and the ammonium bicarbonate solution C was added at a feed rate of 90 L / h, the stirring speed was 400 rpm, the reaction temperature was 38° C., the pH value was maintained between 7.5 and 7.8, and the first coprecipitation reaction was carried out. After the reaction for 4 hours, a stable crystal nucleus structure was obtained;

[0068] After obtaining the core structure, Figure 1 As shown, solution B is continuously injected into solution A at a feed rate of 20 L / h, the feed rate of solution A (i.e., the third cobalt-aluminum-zirconium mixed salt solution) after solution B is added is kept unchanged, the feed rate of solution C is adjusted to 58 L / h, the stirring speed is adjusted to 200 rpm, the temperature is 45° C., the pH is maintained between 7.1 and 7.3, and the second coprecipitation reaction is continued. After the reaction is completed, a reaction solution with a product having a D50 of 4.5 μm is obtained;

[0069] Step 3:

[0070] The reaction solution is pumped into a centrifuge and washed using hot water and ammonium bicarbonate as washing media;

[0071] Step 4:

[0072] The washed material is dried in an oven at 110° C. to obtain the aluminum-zirconium co-doped cobalt carbonate, and the aluminum-zirconium co-doped cobalt carbonate includes an aluminum-zirconium co-doped crystal nucleus and an aluminum-zirconium co-doped cobalt carbonate growth layer located on the surface of the crystal nucleus; the doping amount of the aluminum in the cobalt carbonate growth layer increases from the inside to the outside.

[0073] Figure 2 The EDS graph of zirconium on the surface of aluminum-zirconium co-doped cobalt carbonate provided in Example 1 is shown. Figure 2 It can be seen that the aluminum-zirconium co-doped cobalt carbonate obtained by the preparation method provided by the present invention achieves uniform doping of zirconium.

[0074] Figure 3 The EDS graph of aluminum in the aluminum-zirconium co-doped cobalt carbonate surface provided in Example 1 is shown. Figure 3 It can be seen that the aluminum-zirconium co-doped cobalt carbonate obtained by the preparation method provided by the present invention has a uniform surface after the aluminum content reaches 10,000 ppm in the later stage, and no precipitation has occurred on the surface.

[0075] Example 2

[0076] This embodiment provides an aluminum-zirconium co-doped cobalt carbonate, and the preparation method of the aluminum-zirconium co-doped cobalt carbonate is as follows:

[0077] Step 1:

[0078] Prepare a first cobalt-aluminum-zirconium mixed salt solution A (chloride salt), wherein the concentration of Co salt (cobalt chloride) in solution A is 1.9 mol / L, the concentration of aluminum salt (aluminum sulfate) in solution A is 12 mmol / L, the concentration of Zr salt (zirconium sulfate) in solution A is 5.4 mmol / L, and the volume of solution A is 960 L;

[0079] A second cobalt-aluminum-zirconium mixed salt solution B (chloride salt) is prepared, wherein the concentration of the Co salt in solution B is 1.9 mol / L, the concentration of the aluminum salt (aluminum sulfate) in solution B is 40 mmol / L, the concentration of the Zr salt (zirconium sulfate) in solution B is 5.4 mmol / L, and the volume of solution B is 800 L;

[0080] The concentration of the precipitant ammonium bicarbonate solution C is prepared to be 3 mol / L;

[0081] Step 2:

[0082] The first cobalt-aluminum-zirconium mixed salt solution A was added to the reactor at a feed rate of 40 L / h and the ammonium bicarbonate solution C was added at a feed rate of 90 L / h, the stirring speed was 200 rpm, the reaction temperature was 50° C., the pH value was maintained between 7.4 and 7.6, and the first coprecipitation reaction was carried out. After the reaction time was 8 hours, a stable crystal nucleus structure was obtained;

[0083] After obtaining the crystal nucleus structure, solution B was continuously injected into solution A at a feed rate of 30 L / h, the feed rate of solution A (i.e., the third cobalt-aluminum-zirconium mixed salt solution) after adding solution B was kept unchanged, the feed rate of solution C was adjusted to 80 L / h, the stirring speed was adjusted to 150 rpm, the temperature was 35° C., the pH was maintained between 7.1 and 7.3, and the second coprecipitation reaction was continued. After the reaction was completed, a reaction solution with a product of D50 of 10 μm was obtained;

[0084] Step 3:

[0085] The reaction solution is pumped into a centrifuge and washed using hot water and ammonium bicarbonate as washing media;

[0086] Step 4:

[0087] The washed material is dried in an oven at 110° C. to obtain the aluminum-zirconium co-doped cobalt carbonate, and the aluminum-zirconium co-doped cobalt carbonate includes an aluminum-zirconium co-doped crystal nucleus and an aluminum-zirconium co-doped cobalt carbonate growth layer located on the surface of the crystal nucleus; the doping amount of the aluminum in the cobalt carbonate growth layer increases from the inside to the outside.

[0088] Example 3

[0089] This embodiment provides an aluminum-zirconium co-doped cobalt carbonate, and the preparation method of the aluminum-zirconium co-doped cobalt carbonate is as follows:

[0090] Step 1:

[0091] A first cobalt-aluminum-zirconium mixed salt solution A is prepared, wherein the concentration of the Co salt (cobalt chloride) in the solution A is 1.8 mol / L, the concentration of the aluminum salt (aluminum sulfate) in the solution A is 10.8 mmol / L, the concentration of the Zr salt (zirconium sulfate) in the solution A is 4.8 mmol / L, and the volume of the solution A is 960 L;

[0092] A second cobalt-aluminum-zirconium mixed salt solution B (chloride salt) is prepared, wherein the concentration of the Co salt (cobalt chloride) in solution B is 1.8 mol / L, the concentration of the aluminum salt (aluminum sulfate) in solution B is 37.5 mmol / L, the concentration of the Zr salt (zirconium sulfate) in solution B is 4.8 mmol / L, and the volume of solution B is 800 L;

[0093] The concentration of the precipitant ammonium bicarbonate solution C is prepared to be 2.5 mol / L;

[0094] Step 2:

[0095] The first cobalt-aluminum-zirconium mixed salt solution A was added to the reactor at a feed rate of 40 L / h and the ammonium bicarbonate solution C was added at a feed rate of 90 L / h, the stirring speed was 400 rpm, the reaction temperature was 38° C., the pH value was maintained between 7.5 and 7.8, and the first coprecipitation reaction was carried out. After the reaction for 4 hours, a stable crystal nucleus structure was obtained;

[0096] After obtaining the crystal nucleus structure, solution B was continuously injected into solution A at a feed rate of 38 L / h, the feed rate of solution A (i.e., the third cobalt-aluminum-zirconium mixed salt solution) after adding solution B was kept unchanged, the feed rate of solution C was adjusted to 58 L / h, the stirring speed was adjusted to 200 rpm, the temperature was 45° C., the pH was maintained between 7.1 and 7.3, and the second coprecipitation reaction was continued. After the reaction was completed, a reaction solution with a product having a D50 of 4.5 μm was obtained;

[0097] Step 3:

[0098] The reaction solution is pumped into a centrifuge and washed using hot water and ammonium bicarbonate as washing media;

[0099] Step 4:

[0100] The washed material is dried in an oven at 110° C. to obtain the aluminum-zirconium co-doped cobalt carbonate, and the aluminum-zirconium co-doped cobalt carbonate includes an aluminum-zirconium co-doped crystal nucleus and an aluminum-zirconium co-doped cobalt carbonate growth layer located on the surface of the crystal nucleus; the doping amount of the aluminum in the cobalt carbonate growth layer increases from the inside to the outside.

[0101] Example 4

[0102] The difference between this embodiment and embodiment 1 is that in step 1 of this embodiment, the concentration of aluminum salt in solution A is 15 mmol / L.

[0103] The rest of the preparation methods and parameters were the same as those in Example 1.

[0104] Example 5

[0105] The difference between this embodiment and embodiment 1 is that in step 1 of this embodiment, the concentration of aluminum salt in solution A is 5 mmol / L.

[0106] The rest of the preparation methods and parameters were the same as those in Example 1.

[0107] Example 6

[0108] The difference between this embodiment and embodiment 1 is that in step 1 of this embodiment, the concentration of aluminum salt in solution B is 30 mmol / L.

[0109] The rest of the preparation methods and parameters were the same as those in Example 1.

[0110] Example 7

[0111] The difference between this embodiment and Embodiment 1 is that in step 1 of this embodiment, the concentration of the aluminum salt in solution B is 45 mmol / L.

[0112] The remaining preparation methods and parameters are the same as those in Embodiment 1.

[0113] Embodiment 8

[0114] The difference between this embodiment and Embodiment 1 is that in step 1 of this embodiment, the concentrations of the zirconium salt solution in solution A and solution B are both adjusted to 10 mmol.

[0115] The remaining preparation methods and parameters are the same as those in Embodiment 1.

[0116] Embodiment 9

[0117] The difference between this embodiment and Embodiment 1 is that in step 1 of this embodiment, the concentrations of the zirconium salt solution in solution A and solution B are both adjusted to 2 mmol.

[0118] The remaining preparation methods and parameters are the same as those in Embodiment 1.

[0119] Comparative Example 1

[0120] The difference between this comparative example and Embodiment 1 is that in step 1 of this comparative example, the concentrations of the aluminum salt in solution A and solution B are replaced, that is, the concentration of the aluminum salt in solution A is 38.77 mmol / L, and the concentration of the aluminum salt in solution B is 11.36 mmol / L.

[0121] The remaining preparation methods and parameters are the same as those in Embodiment 1.

[0122] [Preparation and Performance Test of Lithium Cobalt Oxide Cathode Material]

[0123] Preparation of lithium cobalt oxide cathode material:

[0124] The prepared aluminum-zirconium co-doped cobalt carbonate was heated to a calcination temperature of 750 °C at a heating rate of 8 °C / min and then held for 90 min to obtain aluminum-zirconium co-doped cobalt tetroxide;

[0125] Weigh the cobalt tetroxide precursor materials and lithium carbonate provided in Embodiments 1-8 and Comparative Examples 1-4 according to the molar ratio of lithium to cobalt of 1.025, mix them evenly, and then sinter them in a box furnace at 1100 °C for 9 h in an air atmosphere; the primary sintered product after sintering was crushed, iron-removed, and sieved to obtain the lithium cobalt oxide cathode material.

[0126] Performance test of lithium cobalt oxide cathode material:

[0127] Disperse 80 wt% of the positive electrode active material (lithium cobaltate prepared in Examples 1-8 and Comparative Examples 1-4 respectively as the positive electrode active material), 10 wt% of Super-P, and 10 wt% of polyvinylidene fluoride (PVDF) in an N-methylpyrrolidone (NMP) solution to prepare an electrode slurry, coat it on an aluminum foil, and obtain a positive electrode after drying;

[0128] A lithium sheet serves as the negative electrode;

[0129] The separator is a PP microporous membrane with a diameter of Φ19 (Celgard 2400);

[0130] The composition of the electrolyte is: 1 M LiPF6 and a mixture of EC, DMC, and EMC (EC:DMC:EMC volume ratio = 1:1:1).

[0131] Assemble the above positive electrode, separator, negative electrode, and electrolyte to obtain a button cell.

[0132] Perform performance tests on the lithium-ion batteries provided in Examples 1-9 and Comparative Example 1. The test conditions are: under an electrochemical window of 3.0 - 4.6 V, perform a cycle test at a charge-discharge rate of 1C, and test the capacity retention rate after 100 cycles. The test results are shown in Table 1.

[0133] Table 1

[0134]

[0135]

[0136] It can be concluded from Table 1 that:

[0137] (1) The lithium cobaltate batteries prepared with the lithium cobaltate positive electrode material precursors provided in Examples 1-3 of the present invention have a relatively high capacity and excellent cycle stability at 4.6 V;

[0138] (2) By comparing Example 1 with Examples 4 and 5, it can be seen that in the preparation method of the present invention, the concentration of the aluminum salt in Solution A will affect the performance of the lithium cobaltate battery prepared with the lithium cobaltate positive electrode material precursor; when the concentration of the aluminum salt is relatively low, the capacity is relatively low and the capacity retention rate does not change significantly; when the concentration of the aluminum salt is relatively high, the capacity retention rate will deteriorate. This is because as the Al doping amount increases, the battery capacity gradually increases, but when it reaches a certain amount, it will destroy the crystal structure of the original material, resulting in a deterioration of the cycle performance and a corresponding reduction in the capacity retention rate;

[0139] (3) By comparing Example 1 with Examples 6 and 7, it can be seen that in the preparation method of the present invention, the solubility of aluminum in the B solution will affect the performance of the lithium cobalt oxide battery prepared from the lithium cobalt oxide positive electrode material precursor; when the aluminum concentration in the B solution is low, the capacity becomes smaller but the capacity retention rate does not decrease significantly; when the aluminum concentration in the B solution is high, the cycle performance will deteriorate. This is because the battery capacity gradually increases with the increase of the Al doping amount, but when it reaches a certain amount, it will destroy the crystal structure of the original material, resulting in a corresponding decrease in the cycle performance and capacity retention rate;

[0140] (4) By comparing Example 1 with Examples 8 and 9, it can be seen that the solubility of aluminum in the A / B solution of the preparation method of the present invention will affect the performance of the lithium cobalt oxide battery prepared with the lithium cobalt oxide positive electrode material precursor; when the aluminum concentration in the A / B solution is low, the capacity becomes smaller but the capacity retention rate does not decrease significantly; when the aluminum concentration in the A / B solution is high, the cycle performance will deteriorate. This is because the battery capacity gradually increases with the increase of the Al doping amount, but when it reaches a certain amount, it will destroy the crystal structure of the original material, resulting in a corresponding decrease in the cycle performance and capacity retention rate;

[0141] (5) By comparing Example 1 with Comparative Example 1, it can be seen that the lithium cobalt oxide positive electrode material precursor provided by the present invention is formed by uniformly doping cobalt oxide with aluminum gradient doping and zirconium doping, and the Al doping increases from the inside to the outside, while the comparative example is higher inside and outside, and the B-dissolved aluminum does not play a significant gradient role, resulting in poor cycle performance. Therefore, the positive electrode material prepared from the obtained lithium cobalt oxide positive electrode material precursor has higher stability and better electrical properties under high voltage.

[0142] In summary, the preparation method provided by the present invention obtains a stable crystal nucleus structure, and then regulates the cobalt, aluminum, zirconium mixed salt solution, which can better ensure that the aluminum in the cobalt carbonate particles gradually increases as the particles grow, and in the second coprecipitation preparation process, the second cobalt, aluminum, zirconium mixed salt solution with a higher aluminum salt concentration is directly added to the aluminum salt solution with a lower aluminum salt concentration at a fixed feed flow rate, which can continuously increase the concentration of aluminum salt in the first cobalt, aluminum, zirconium solution without affecting the normal progress of the reaction, and at the same time, the zirconium salt concentration is kept consistent in the two mixed salt solutions, thereby achieving uniform doping of zirconium; thereby, in the obtained aluminum-zirconium co-doped cobalt carbonate material, the aluminum doping amount gradually increases in the cobalt carbonate growth layer, and the zirconium presents a uniform doping pattern, which can not only ensure the structural stability of the cobalt carbonate material, but also effectively improve the cycle performance of the lithium cobalt oxide material under high voltage, while also ensuring the good performance of the first effect of the lithium cobalt oxide material; and the preparation method does not require an additional preparation process and is simple to operate.

[0143] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing aluminum-zirconium co-doped cobalt carbonate, characterized in that: The preparation method comprises the following steps: Adding the first cobalt-aluminum-zirconium mixed salt solution and the precipitant solution into a reaction container in parallel to perform a first coprecipitation reaction to obtain a crystal nucleus structure; After the first coprecipitation reaction is completed, the second cobalt-aluminum-zirconium mixed salt solution is continuously added to the first cobalt-aluminum-zirconium mixed salt solution to obtain a third cobalt-aluminum-zirconium mixed salt solution, and the third cobalt-aluminum-zirconium mixed salt solution and the precipitant solution are simultaneously added to the reaction container in parallel to perform a second coprecipitation reaction to obtain the zirconium-aluminum co-doped cobalt carbonate; Among them, the concentration of aluminum salt in the first cobalt-aluminum-zirconium mixed salt solution is lower than the concentration of aluminum salt in the second cobalt-aluminum-zirconium mixed salt solution, and the concentration of zirconium salt in the first cobalt-aluminum-zirconium mixed salt solution is consistent with the concentration of zirconium salt in the second cobalt-aluminum-zirconium mixed salt solution; the feed flow rate of the third cobalt-aluminum-zirconium mixed salt solution is consistent with the feed flow rate of the first cobalt-aluminum-zirconium mixed salt solution in the first coprecipitation reaction process.

2. The preparation method according to claim 1, characterized in that: The concentration of the first cobalt-aluminum-zirconium mixed salt solution and the concentration of the second cobalt-aluminum-zirconium mixed salt solution are each independently 1.8 to 1.9 mol / L; Preferably, the concentration of zirconium salt in the first cobalt-aluminum-zirconium mixed salt solution is 4.8-5.4 mmol / L.

3. The preparation method according to claim 1 or 2, characterized in that: The concentration of aluminum salt in the first cobalt-aluminum-zirconium mixed salt solution is 10.8-12 mmol / L; Preferably, the concentration of aluminum salt in the second cobalt-aluminum-zirconium mixed salt solution is 37.5-40 mmol / L.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The feed flow rate L2 of the second cobalt-aluminum-zirconium mixed salt solution satisfies: 20L / h≤L2<L1, wherein the feed flow rate of the first cobalt-aluminum-zirconium mixed salt solution is L1.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The reaction temperatures of the first coprecipitation reaction and the second coprecipitation reaction are each independently 35 to 50° C.; Preferably, the pH values ​​of the first coprecipitation reaction and the second coprecipitation reaction are independently 6.9 to 8; Preferably, the stirring speeds of the first coprecipitation reaction and the second coprecipitation reaction are each independently 150 to 450 rpm.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Adding the first cobalt-aluminum-zirconium mixed salt solution and the precipitant solution into the reaction container at a feed flow rate of L1 in parallel to perform a first coprecipitation reaction to obtain a crystal nucleus structure; A second cobalt-aluminum-zirconium mixed salt solution is continuously added to the first cobalt-aluminum-zirconium mixed salt solution, and the feed flow rate L2 of the second cobalt-aluminum-zirconium mixed salt solution satisfies: 20L / h≤L2<L1, to obtain a third cobalt-aluminum-zirconium mixed salt solution, and the third cobalt-aluminum-zirconium mixed salt solution and the precipitant solution are simultaneously added to the reaction container in parallel to perform a second coprecipitation reaction to obtain the zirconium-aluminum co-doped cobalt carbonate; Among them, the concentration of aluminum salt in the first cobalt-aluminum-zirconium mixed salt solution is 10.8-12 mmol / L, and the concentration of aluminum salt in the second cobalt-aluminum-zirconium mixed salt solution is 37.5-40 mmol / L; the concentration of zirconium salt in the first cobalt-aluminum-zirconium mixed salt solution is consistent with the concentration of zirconium salt in the second cobalt-aluminum-zirconium mixed salt solution, and the concentration of zirconium salt in the first cobalt-aluminum-zirconium mixed salt solution is 4.8-5.4 mmol / L; the feed flow rate of the third cobalt-aluminum-zirconium mixed salt solution is consistent with the feed flow rate of the first cobalt-aluminum-zirconium mixed salt solution in the first coprecipitation reaction process.

7. An aluminum-zirconium co-doped cobalt carbonate, characterized in that: The aluminum-zirconium co-doped cobalt carbonate is prepared by the preparation method according to any one of claims 1 to 6; The aluminum-zirconium co-doped cobalt carbonate comprises an aluminum-zirconium co-doped crystal core and an aluminum-zirconium co-doped cobalt carbonate growth layer located on the surface of the crystal core; the doping amount of the aluminum in the cobalt carbonate growth layer increases from the inside to the outside.

8. A cobalt trioxide, characterized in that: The cobalt trioxide is obtained by sintering the aluminum-zirconium co-doped cobalt carbonate as claimed in claim 7.

9. A lithium cobalt oxide, characterized in that: The lithium cobalt oxide is obtained by mixing and sintering the cobalt trioxide as claimed in claim 8 and a lithium source.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium cobalt oxide as claimed in claim 9.